Tumor necrosis factor alpha, citrullination, and peptidylarginine deiminase 4 in lung and joint inflammation. Issue 1 (December 2016) - Bawadekar, Mandar; Gendron-Fitzpatrick, Annette; Rebernick, Ryan; Shim, Daeun; Warner, Thomas; Nicholas, Anthony; Lundblad, Lennart; Thompson, Paul; Shelef, Miriam
Abstract Background The relationship between lung and joint inflammation in rheumatoid arthritis is poorly understood. Lung inflammation with resultant protein citrullination may trigger anti-citrullinated protein antibodies, inflammation, and arthritis. Alternatively, lung and joint inflammation may be two manifestations of a single underlying pathology. The lung has increased citrullination and TNF-α levels are high in rheumatoid arthritis; however, it is unknown if TNF-α can induce lung protein citrullination. The citrullinating enzyme peptidylarginine deiminase 4 (PAD4) exacerbates TNF-α-induced arthritis, but a role for PAD4 in lung citrullination and TNF-α-induced lung inflammation has not been explored. Our aim was to use TNF-α-overexpressing mice to clarify the intersection of TNF-α, citrullination, PAD4, arthritis, and lung inflammation. Methods Lung protein citrullination in wild-type mice, mice that overexpress TNF-α systemically (TNF+ ), TNF+ PAD4+/+, and TNF+ PAD4-/- mice was quantified by both gel electrophoresis using a citrulline probe and western blot. Hematoxylin and eosin (H&E)-stained lung sections from TNF+ PAD4+/+ and TNF+ PAD4-/- mice were scored for lung inflammation. H&E-stained ankle joint sections from mice that overexpress TNF-α only in the lungs were assessed for arthritis. Results TNF+ mice have increased lung protein citrullination. TNF+ PAD4-/- mice do not have significantly reduced lung protein citrullination, but do have decreased lung inflammation compared to TNF+ PAD4+/+ mice. Mice that overexpress TNF-α only in the lungs do not develop arthritis. Conclusions PAD4 exacerbates lung inflammation downstream of TNF-α without having a major role in generalized protein citrullination in inflamed lungs. Also, TNF-α-induced lung inflammation is not sufficient to drive murine arthritis.